FACTORS INFLUENCING THE EVOLUTION OF HIGHER EDUCATION GRADUATION IN ROMANIA, SPOTLIGHTING ECONOMIC STUDIES - Roxana Hatos (Annals of the University of Oradea: Economic Science, 2016)
The dynamics of the higher education access is one of the challenges that Europe has to face regarding education and labour market challenges. Romania has to deal with the expansion of higher education with its particularities. Regardless the specificities, expansion of higher education in Romania and in European countries, the number of higher education graduates have a constant upward trend at EU level. The population of graduates in Romania face the most dramatic developments: the number of graduates almost triples between 2003 and 2008, when it reached a peak due to the overlapping of the last generation pre-Bologna and the first generation Bologna followed by a veritable collapse in 2011 and 2012. According to European statistics, such catastrophic changes have not happened in any European country, even in crisis conditions. In this paper we investigate the evolution of higher education graduation in Romania comparatively with the European level rates. We highlight the fast expansion followed by contraction noted for most domains of study in Romania, nonetheless the most accentuated for economic sciences. Investigating the factors that influence this evolution we could neither support nor fully reject the impact of demographic decline of young population in Romania, nor the decline in graduation rates of secondary level education. These results are affected by the high percentage of non-traditional students in Romania, students that graduated high-school or have had other studies before 1990. These people wanted to complete their studies according to their occupation or in order to have access to better jobs, with better salaries. Also the adoption of the Bologna reform influenced the apparition of a peak in higher education graduation in 2008-2009. In the final section we focus on the evolution of number of students and graduates of Economic Studies from University of Oradea, proving that the same trends as at national level are present. However, in order to better understand future trends such an analyses should also integrate information regarding employability of graduates depending on domain or field of study (evolutions of the labour market), information at institution level such as endowments and prestige, international migration of secondary school graduates. Understating such trends at both national, field and institution level are bound to better prepare universities to face future challenges.